Hollow porous silicon nanospheres with 3D SiC@C coating as high-performance anodes. (February 2023) - Chen, Zehan; Jia, He; Hoeppener, Stephanie; Friebe, Christian; Wang, Jiande; Chanteux, Géraldine; Xie, Dongjiu; Lu, Yan; Vlad, Alexandru; Schubert, Ulrich S.; Gohy, Jean-François
Graphical abstract: Highlights: A facile synthetic route using a polymer template has been developed to prepare hollow porous Si nanospheres with 3D SiC on C coating. The polymer template prevents the waste of organic components and the post-introduction of foreign carbon sources during the synthesis of the hollow Si nanospheres. High capacity (3200 mAh/g) and exceptional stability upon cycling (decay of 0.7‰ per cycle) are obtained for the anodes prepared from the hollow Si nanospheres. Abstract: Silicon is regarded as one of the most promising anode candidates for next-generation Li-ion batteries because of its high theoretical capacity (4200 mAh g −1 ). However, the main challenge for the practical application of Si anodes is the huge volume change during (de)alloying with lithium, which leads to the pulverization of the active material and severe loss of electrical contact after cycling. Here, we develop hollow porous silicon nanospheres with three-dimensional carbon coating and SiC transition interlayer (C@SiC@Si@SiC@C) via a simple and straightforward polymer-directed strategy in order to tackle the challenges met with Si anodes. The accordingly synthesized C@SiC@Si@SiC@C anode shows high utilization of the active substance, high measured capacity (3200 mAh g −1 ) with almost 100% Coulombic efficiency and stable cycling performance (0.7‰ per cycle decay rate at 0.2C). Such superior performances are related to the uniquely designed structure. Firstly, the 3D carbon coating provides high electronic conductivity, and extremely small size of silicon shortens the diffusion distance for Li ions and electrons. Secondly, the stable cyclability originates from the nanoscale silicon particles reinforced by a SiC transition interlayer which effectively prevents fracture and provides robust outer layers, respectively.